Investigasi takarir digital pada pola-pola linguistik dan perspektif mahasiswa - Esra Perangin-angin; Ernawati Br Surbakti; Sri Dinanta Beru Ginting; Rusda Nita Nelly Manurung (Universitas Mulawarman, 2026)
This study examines semantic errors in the use of the Indonesian word acuh, which is frequently misinterpreted as “not to care.” The focus of the research is on captions posted by the Instagram account Tribun Medan Daily. The objective of the study is to describe the forms of these semantic inaccuracies and to analyze public perceptions of the word’s meaning. The research employs a descriptive qualitative approach. Data were collected from Instagram captions and a closed-ended questionnaire administered to students of Universitas Prima Indonesia. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña. The findings indicate that 61.5% of respondents interpreted the word acuh as “not to care,” which contradicts its official definition in the Kamus Besar Bahasa Indonesia (KBBI).The discrepancy in lexical meaning, as observed in the word acuh, along with morphophonemic inaccuracies such as the use of nonstandard forms, does not merely reflect individual linguistic errors; rather, it constitutes a systemic phenomenon that can be explained through multiple linguistic frameworks, including structural, generative, functional, and cognitive perspectives.